Identification of Human Endogenous Retrovirus-Specific T Cell Responses in Vertically HIV-1-Infected Subjects - Tandon, Ravi; SenGupta, Devi; Ndhlovu, Lishomwa C.; Vieira, Raphaella G. S.; Jones, R. Brad; York, Vanessa A.; Vieira, Vinicius A.; Sharp, Elizabeth R.; Wiznia, Andrew A.; Ostrowski, Mario A.; Rosenberg, Michael G.; Nixon, Douglas F. (Journal of Virology, 2011)
OA Article Usage Stats Services JVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue JVI About JVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0022-538X Online ISSN: 1098-5514 Copyright © 2014 by the American Society for Microbiology. For an alternate route to JVI .asm.org, visit: JVI